DOES MARKETING CAPABILITY MEDIATE THE RELATIONSHIP BETWEEN ENTREPRENEURIAL ORIENTATION AND SME PERFORMANCE - Lestari, Dewi (LPPM-ITEBA, 2025)
The purpose of this study was to analyze the role of marketing capabilities and dimensions of entrepreneurial orientation on the performance of SMEs in the city of Padang. All leaders or owners of SMEs in the city of Padang are the population of this study. The sampling technique used in this research is non-probability sampling with accidental sampling technique. Samples were taken as many as 152 samples. This research uses SEM-PLS. The results showed that there was a positive and significant influence of the entrepreneurial orientation dimension on the marketing capability of SMEs, the entrepreneurial orientation dimension had a positive and significant effect on the performance of SMEs in the city of Padang. marketing capability has a significant effect on the performance of SMEs. And there is a positive and significant influence between the dimensions of entrepreneurial orientation on the performance of SMEs in the city of Padang through marketing capabilities. The managerial implications of this research are discussed later.